Age-related differences in effectiveness of item restudy choices: the role of value. Issue 1 (2nd January 2018) - Li, Ping; Zhang, Yuchi; Li, Weijian; Li, Xinyu
ABSTRACT: We examined the effect of value on effectiveness of restudy choices in younger and older adults by using an honor or dishonor procedure. In the honor condition, participants restudied the half of the items that they selected for restudy. In the dishonor condition, participants restudied the half of the items that they did not select for restudy. The results showed that younger adults restudied more low-value (1-point) items that they had rated as least-well learned, while older adults restudied more high-value (5-point) items. For younger adults, 1-point-value item performance in the honor condition was reliably higher than it was in the dishonor condition. For older adults, 5-point-value items performance in the honor condition was reliably higher than it was in the dishonor condition. These results suggest that older adults can exert effective restudy choices like younger adults when item value is manipulated.